Peers’ Influence Matters: Evidence from Corporate Dividend Policy Decisions - Muhammad Mudassar Anwar; Filza Hameed; Mubashar Hassan Zia (International Journal of Business and Economic Affairs, 2023)
Peer effect impacts financial decision making. Seeing that, the current study investigates the impact of peers’ while deciding about dividend policy. For this purpose, two sets such as firm specific as well peer firms’ specific characteristics (independent variables) used. The current study utilized OLS regression fixed effect model. To check correlated effect the study used two vital macro-economic variables stock market return as well interest rate. The results of the study revealed significant contributions of peers while determining firm’s dividend policy decisions. The current study results too confirmed the impact of peers’ on firm’s dividend policy in the context of Pakistan. Limitations as well future directions are discussed.